2021
DOI: 10.3390/ijerph18041730
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Electromagnetic Fields and Health Surveillance according to the European Directive 2013/35/EU

Abstract: In the European Union, health surveillance (HS) of electromagnetic fields (EMF)-exposed workers is mandatory according to the Directive 2013/35/EU, aimed at the prevention of known direct biophysical effects and indirect EMF’s effects. Long-term effects are not addressed in the Directive as the evidence of a causal relationship is considered inadequate. Objectives of HS are the prevention or early detection of EMF adverse effects, but scant evidence is hitherto available on the specific procedures. A first iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…In line with earlier research and considering these limitations of our study it should still be considered useful to evaluate the occurrence of these health complaints during health surveillance of MRI personnel (8). The importance of investigating these symptoms is not only related to their possible association with EMF exposure during MRI activities, as previously reported (12)(13)(14), but it should be considered that a systematic collection of these symptoms may help the occupational physicians responsible for the health surveillance of MRI personnel in identifying groups of subjects at "particular risk, " as indicated in European Directive 2013/35 (8). In fact, many of these symptoms, and in particular core symptoms, can be considered sensory effects of exposure to magnetic fields, and they are particularly related to the performance of physical movements within a static magnetic field.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In line with earlier research and considering these limitations of our study it should still be considered useful to evaluate the occurrence of these health complaints during health surveillance of MRI personnel (8). The importance of investigating these symptoms is not only related to their possible association with EMF exposure during MRI activities, as previously reported (12)(13)(14), but it should be considered that a systematic collection of these symptoms may help the occupational physicians responsible for the health surveillance of MRI personnel in identifying groups of subjects at "particular risk, " as indicated in European Directive 2013/35 (8). In fact, many of these symptoms, and in particular core symptoms, can be considered sensory effects of exposure to magnetic fields, and they are particularly related to the performance of physical movements within a static magnetic field.…”
Section: Discussionsupporting
confidence: 63%
“…The risk related to occupational exposure to these types of EMFs needs to be evaluated, as it is for other occupational risks, in order to ensure adequate occupational safety and health (OSH) of MRI personnel (8). Among the effects to be considered for appropriate preventive interventions, it should be noted that, according to the scientific literature, various subjective sensory symptoms have been reported for MRI personnel (1,(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…It is further suggested that susceptibility to EMF is influenced by the fundamental medical condition [ 4 , 6 ]. This was also true when translated to in vitro experiments, in which only osteoblasts with an initial low capacity for matrix mineralization responded to EMF treatment [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the sensitivity of human health to electromagnetic fields (EMF) have accumulated around the globe and manifest clinically as electromagnetic hypersensitivity (EHS) with broad-spectrum symptoms in multiple organs [ 1 , 2 , 3 ]. The European Union acknowledged and tackled EHS concerns in the Directive 2013/35/EU, recommending exposure levels of maximum 0.1 mT for public exposure, up to 1 mT for workers at particular risk (WPR), and accepts levels of 3–6 mT in temporary situations [ 4 , 5 ]. Similarly to WPR, medically preconditioned individuals were suggested to be more susceptible to EHS as their survival rate was found to decrease under EMF exposure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this indicator was higher in women [37]. The purpose of monitoring of EMF side effects is to identify electrosensitive workers with increased susceptibility [38].…”
Section: Experience Of Studying Of Medical Personnel Health Under the Influence Of Non-ionizing Radiationmentioning
confidence: 99%